Aesthetic Judgment, Morality and Cancel Culture with reference to Alessandro Ferrara's thought (Itinera, 2024)
Alessandro Ferrara's moral philosophy is centered on the concept of “exemplarity”, that is conceived of as an aesthetic notion. I aim to use this kind of approach, that I interpret relying on the reference to the inductive inference, in order to deal with the issues of the “cancel culture”.